HUBUNGAN PENGETAHUAN, PERSEPSI, DAN KEYAKINAN DENGAN PENERIMAAN VAKSIN COVID-19 PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS DANA TAHUN 2022 - Erfin Sekarwati; Suhadi Suhadi; La Ode Muhamad Sety (Endemis Journal, 2022)
To cope with the covid-19 pandemic, authorities have devised strategies to protect communities from the contagion and effects of covid-19. One is the covid19 vaccine program given to society. The covid-19 vaccination is supposed to reduce or damage the chain of contagion, Lower morbidity and mortality and can gain herd participation in community groups. This study aims to find out the relation of knowledge, perception and belief with the acceptance of the covid-19 vaccine on people in the 2022 labor district of the Treasury. This study USES an analtic quantitative study with a sectional study approach. The population in this study is all the people that live in the workspace of the Dana center. The sample in this study totaled 333 ages 12-59. Selection of samples is made using a random sampling cluster. The analysis used was the variate union and Bivariate with chi square test. Research shows that there is no link between knowledge (0.877 > 0.05) And perception (1,000 > 0.05) with acceptance of the covid-19 vaccine. Instead there is a confident relationship (0.013 < 0.05) with the acceptance of the covid-19 vaccine. The conclusion in this study of variable knowledge and perception is no correlation and belief variable has nothing to do with receiving the covid-19 vaccine on people in the labor district of the Treasury in 2022.